TEACHING FOREIGN LANGUAGES TO STUDENTS ACCORDING TO THEIR SOCIAL BACKGROUND (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
In today’s globalized world, the ability to communicate across cultures is essential, making foreign language education a crucial component of modern curricula. However, effective language teaching extends beyond just vocabulary and grammar; it must also consider the students' diverse social backgrounds. Understanding the social context in which a student lives can significantly influence how they learn and use a new language. This article explores the importance of tailoring foreign language teaching to students’ social backgrounds and provides strategies for educators to better support diverse learners.